Trauma-Informed Pedagogies A Guide for Responding to Crisis and Inequality in Higher Education - Thompson, Phyllis; Carello, Janice (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book centers equity in the approach to trauma-informed practice and provides the first evidence-based guide to trauma-informed teaching and learning in higher education. The book is divided into four main parts. Part I grounds the collection in an equity approach to trauma-informed care and illustrates one or more trauma-informed principles in practice. Chapters in Part II describe trauma-informed approaches to teaching in specific disciplines. In Part III, chapters demonstrate trauma-informed approaches to teaching specific populations. Part IV focuses on instruments and strategies for assessment at the institutional, organizational, departmental, class, and employee levels. The book also includes a substantial appendix with more than a dozen evidence-based and field-tested tools to support college educators on their trauma-informed teaching journey. Phyllis Thompson is Associate Professor and Director of Women's, Gender, and Sexuality Studies at East Tennessee State University, USA. Thompson co-edited Lessons from the Pandemic: Trauma-Informed Approaches to College, Crisis, Change and publishes on women's medicinal recipe books. Janice Carello is Assistant Professor and MSW Program Director at Edinboro University, USA. She co-edited Lessons from the Pandemic and Trauma and Human Rights and publishes trauma-informed teaching and learning resources on her blog: traumainformedteaching.blog. "Carello and Thompson have created a much-needed reference describing trauma-informed care for everyone working in higher education. Anyone who serves as faculty, administrators, or staff in academic settings must understand what this means for the ways in which they teach and interact with their students." -Sandra L. Bloom, Associate Professor, Health Management and Policy, Drexel University, USA "This book is nothing short of a miracle for higher education professionals who are eager to answer the call for trauma-informed change in a tumultuous world. It provides thoughtful, evidence-based approaches to light the path ahead, addressing the seismic shift in college student demographics, the knowledge gained from two decades of scientific studies into adversity and brain development, and the urgent need for inclusion and equity in higher education. As a whole, this book is simply indispensable." -Karen Oehme, Director, Student Resilience Project, Florida State University, USA, and Chairperson, Academic Resilience Consortium (ARC).
Introduction -- Section I. INFUSING TRAUMA-INFORMED PRINCIPLES -- 1. Employing Trauma-Informed Principles through a Feminist Model of Practice -- 2. Leveraging the Neuroscience of Now to Cultivate a Pedagogy of Purpose and Empowerment -- 3. Building Resiliency through the Trauma Informed Classroom -- 4. Fostering a Spirit of Collaboration by Sharing Power with Students about Course Decisions -- Section II. TRAUMA-INFORMED TEACHING ACROSS THE CURRICULUM -- 5. Processing Critical Knowledge Through Trauma-Informed Musical Travel -- 6. Stumbling My Way to Trauma-Informed Teaching and Learning -- 7. Humanizing Social Work Education: Resetting for Healing Purposes -- 8. Section III. APPROACHES TO WORKING WITH SPECIFIC POPULATIONS -- 9. Trauma-Informed Approaches to Teaching Students with Marginalized Identities during Times of Crisis -- 10. How Trauma-Informed Care Principles Can Contribute to Academic Success for Students in Hispanic-Serving Institutions -- 11. Trauma Informed Educational Practices at Community College -- 12. Not a Hero and not a Stranger: Serving Veterans in Higher Education -- 13. The Benefits of Reflective Journaling during COVID-19: Contingent Faculty Exploring Teaching and Learning during a Crisis -- 14. Developing Trauma-Informed Practice: Coordinating Indigenous Adult Education Programs as a Non-Indigenous Educator -- Section IV. (RE)ASSESSMENT -- 15. Measuring Trauma Resilience in Higher Education Settings -- 16. An Educator's Scope of Practice: How Do I Know What Is Mine? -- 17. What are We Centering?: Developing a Trauma-Informed Syllabus -- 18. Utilizing an Ecological, Trauma-Informed, Equity Lens to Build an Understanding of the Context for and Experience of Self-Care in Higher Education -- Section V. TRAUMA-INFORMED TEACHING TOOLBOX -- 19. Higher Education Trauma Resilience Assessment -- 20. Educator and Department Self-Assessment Tools -- 21. Creation of Brave Space -- 22. First Day of Class Introductions: Trans Inclusion in Teaching -- 23. The Basket: Setting the Stage for Learning -- 24. Moment of Action -- 25. Trauma-Informing your Attendance (Policy) -- 26. No Questions Asked Late Days -- 27. The Revise & Resubmit -- 28. Content Warnings -- 29. Panels and Pain: Teaching with Comics During Times of Trauma -- 30. Partner Exams -- 31. Best Practices for Online Content Design. .
Keywords: Education, Higher; Educational psychology; Teaching; Psychic trauma; Inclusive education; Social psychiatry; Higher Education; Educational Psychology; Pedagogy; Trauma Psychology; Inclusive Education; Clinical Social Work